SISTEM PAKAR DIAGNOSIS PENYAKIT TERNAK SAPI MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEBSITE RESPONSIF: EXPERT SYSTEM FOR DIAGNOSING CATTLE DISEASES USING FORWARD CHAINING METHOD BASED ON RESPONSIVE WEBSITE - Wisnu Dwi Prasetyo; Rizki Wahyudi (Jurnal Teknologi dan Terapan Bisnis, 2019)
The large number of cattle in the Banyumas Regency is not matched by the number of veterinarians. Fisheries and Animal Husbandry Service (Dinkanak) of Banyumas Regency Note 961 cases of sick cows with 39 types of cow disease in 2016, plus the cost of bringing in doctors to treat sick cows is still expensive for farmers. To overcome this problem, this study aims to create a responsive expert website for cow disease diagnosis using the Forward Chaining method to help cattle farmers identify the disease of cattle and its treatment. For the development of expert systems this research uses the RAD (Rapid Application Development) method. To ensure the quality of the expert system, it was tested with three approaches (1) Blackbox testing for functional systems whose results were all functional systems running well (2) testing Validation comparing diagnosis results of Expert Systems with Doctors where expert system diagnosis accuracy was 85% (3) User acceptance testing to test the usefulness and quality of information by questionnaire techniques from a total of 326 respondents, 76% agreed that the application can help diagnose cow disease and the expert system is quite easy to operate.